The Efficacy of NeuroAid™ (MLC601) in Modulating NF-κB Expression and Improving Outcomes in Traumatic Brain Injury: A Preclinical Study - Dedy Chandra Hariyono; Hanis Setyono; Ida Bagus Budhi Surya Adnyana (HM Publisher, 2025)
Background: Traumatic brain injury (TBI) represents a significant global health concern, leading to substantial mortality and long-term disability. The intricate pathophysiology of TBI involves primary mechanical damage followed by a cascade of secondary injury events, including neuroinflammation, apoptosis, and oxidative stress. The nuclear factor kappa B (NF-κB) signaling pathway plays a pivotal role in orchestrating the inflammatory response post-TBI and has emerged as a potential therapeutic target. This preclinical study aimed to investigate the efficacy of NeuroAid™ (MLC601), a traditional herbal medicine, in modulating NF-κB expression and improving outcomes in a rat model of TBI. Methods: This study employed a true experimental in vivo design with a post-test only control group. Male Wistar rats (n=18) were randomly divided into two groups: a control group (n=9) subjected to TBI via a weight-drop method, and an experimental group (n=9) subjected to the same TBI procedure followed by intraperitoneal administration of NeuroAid™ (MLC601) at a dose of 2.5 mg/kg body weight at 5 minutes, 8 hours, and 16 hours post-injury. NF-κB expression in brain tissue samples collected 1 hour after the final dose was assessed using immunohistochemistry and quantified by an immunoreactivity score considering both the intensity and percentage of NF-κB expression. Results: Immunohistochemical analysis revealed the presence of NF-κB expression in both the nucleus and cytoplasm of neurons in both the control and experimental groups. While the experimental group treated with NeuroAid™ (MLC601) exhibited a lower average immunoreactivity score (0.93) compared to the control group (1.29), the difference in NF-κB expression between the two groups was not statistically significant (p = 0.122). Conclusion: In this preclinical study using a Wistar rat model of TBI, the administration of NeuroAid™ (MLC601) did not result in a statistically significant reduction in NF-κB expression compared to the untreated control group. Although a trend towards lower NF-κB expression was observed in the NeuroAid™-treated group, further research with larger sample sizes, different dosages, and extended treatment durations is warranted to fully elucidate the potential therapeutic effects of NeuroAid™ (MLC601) in the management of traumatic brain injury.